The Protagonist’s Struggles in Ahmad Fuadi’s Novel Ranah 3 Warna - Mulyani, Mulyani; Maisarah, Maisarah; Prasetya, Cyndi; Ayudia, Inge (Riviera Publishing, 2023)
This article is the result of a research work on the protagonist’s struggle depicted from Ahmad Fuadi’s novel Ranah 3 Warna. The aims of this research are to reveal the protagonist’s struggles depicted in the novel and to analyze how the protagonist manage his struggles to achieve his goals. The theory applied in this research is adopted from several theories of struggle particularly Krisnananda (2005). The study applied qualitative research method in the process. The finding shows that the three motives of struggle namely struggle for existence, struggle for survival and struggle for power are found in the data. The struggle for existence covers the protagonist’s struggle to get the Senior High School Certificate and to get admission to the State University. The struggle for survival is the protagonist’s struggle to earn his living after the death of his father. The struggle for power covers two aspects namely his struggle for his career as an author and his struggle for the selection of student’s exchange to the United States. Thus, the theory selected does match the data of the study